A Review on Kidney Stones & A Patient Satisfaction Survey of an Ayurvedic Brand to Treat Kidney Stones - Kishor Jain; Dhanshri Kachare; Rajnigandha Gaikwad; Mansi Kalje; Manjusha Kantule; Sudeshana Mohite; Nikita Rodage; Vikas Kandekar; Archana Thikekar (Krupanidhi College of Pharmacy, 2023)
Objective: Kidney stones or nephrolithiasis, is a common problem worldwide. About 12% of the Indian population is estimated to have kidney stones and out of which 50% may end up with loss of kidney functions. In the first part of this article the pathophysiology of kidney stone, its types, risk factors, signs, symptoms, diagnosis and therapy have been discussed. Furthermore, various therapeutic approaches for kidney stone management are also briefly renewed. Methods: The second part of this article discusses a herbal formulation Ren-Cit® successfully used to treat kidney stone, its usage, composition as well as the actions of each of its medicinal constituents. A survey of patients who used Ren-Cit® has been conducted. Finding: The analysis of this survey revealed that 98% of the patients were suffering from kidney stone. Out of these 78% of the patients had hypertension and diabetes. None of the participants observed any side effects from the usage of Ren-Cit®. A total of 76% patients got relief from kidney stone by using Ren-Cit®. Various types of kidney stones diagnosed in these patients had varied composition, viz.; calcium oxalate stone (52%), calcium phosphate stone (16%), uric acid stone (12%), struvite stone (12%) and cystine stone (8%). Novelty: Ren- Cit® ayurvedic formulation proved to be effective on a wide range and types of kidney Stones. Keywords: Kidney Stone; Urolithiasis; Calcium Oxalate; Uric Acid Stone; Calcium Phosphate; Ren-Cit®